Study of demographic and motivation factors towards taking a holiday for Malaysian - Cheng, Fan Fah; Cheng, Seow Voon (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
There are various factors that motivate people into travelling. Just as normal product consumers, tourists undergo several stages of decision making before finally come to conclusion on which destination they will go for. Although there has been numerous studies done on travel motivations, the latest Malaysians travel motivation are somewhat unknown. This study, therefore, will identify the latest demographic variables of Malaysians on their travel motives. In this study, it is important to understand if travel motivations are affected by the demographic variables of Malaysians which includes factors such as genders, age groups and income levels. A 17 items questionnaire was used to measure about 200 respondents on their traveling motivation. It shows that the motives such as ‘to discover new places and things’, ‘to rest’, ‘to build relationships with my family’, ‘to see new cultures’, and ‘to mentally relax” are ranked as the most important motives for Malaysian for travelling. Others attractive reasons that were ranked at the top for travelling abroad are, ‘to visit places that are different’, ‘to satisfy a sense of adventure’, ‘to visit beaches’, ‘to meet new friends’, and ‘to meet interesting people’. It was noted that there were significant different holiday motives based on gender differences in terms of “rest and relax”. It showed that female students inclined more towards ‘rest and relax’ reason. Besides, this study had shown that the age groups too, would influence the perception towards attractiveness, where the concerned age group was from 20 – 29 years. The most significant attractiveness were “sport and adventurer” and “cultural visit” that can also be related to the previous study in which it looked into the perceptions of young visitors. Furthermore, based on the current findings, we can see that travel motives did correlate to each other. However, it was not so strong as after the correlation test, it showed only ‘self-ability enhancement’ was most related to ‘sight-seeing’, and the least related was in between ‘rest & relax’ and ‘sight-seeing’.